Normas internacionales de información financiera y su relación con el comportamiento ético en el proceso contable en contadores Iquitos año 2024 - Cruzalegui Davila, Christopher Segundo (2024)
IFRS and ethical behavior in accounting seek to standardize the global presentation of adequate financial information and promote transparent decisions in the accounting field, the challenges include the adaptation of accountants to the complexity of these regulations and ethical codes, which motivated the development of this research to determine the relationship between the implementation of international financial reporting standards and ethical behavior in the accounting process in Iquitos Accountants year 2024, in order to strengthen the theoretical and practical knowledge in these accounting standards, the ethical implications reflecting transparency and ethical responsibility from the perspective of the Public Accountants of Iquitos, conducting a quantitative observational research and non-experimental relational methodology, with a consistent sample of 95 respondents, selected for convenience from a total population of 865 Chartered Public Accountants of Loreto, determining a significant and positive relationship between both variables in the accounting process in Accountants of Iquitos year 2024, providing a new topic as a background, valuable information on IFRS and ethics in the accounting profession, highlighting that a new data collection instrument is formulated.